The Editorial Note - Editor, Chief (University of Dar es Salaam Library Journal, 2024)
On behalf of the editorial committee and editorial board, I have the privilege to present to you our current issues of June 2024. The tones of the articles in our current issues reflect different LIS dimensions including the application of ICT in teaching and learning, scholarly communication in institutions of higher learning, usage of social media platforms for service delivery and provision of financial services, and the roles and benefits of using human resources information systems (HRIS) in higher learning institutions.